Influence and Application of Poka-Yoke Technique in Automobile Manufacturing System. Issue 1 (June 2021) - Kumar, Rajan; Dwivedi, Ravi Kumar; Dubey, Sudhir K; Singh, Anoop Pratap
Abstract: Manufacturing defect are most important parameter to improve the quality of product for the all-manufacturing industries. In the manufacturing sector day by day new tool and new techniques are apply for the improve the quality manufacturing at low cost. In this practical study discussed about the most important tool of lean manufacturing is poka-yoke (mistake proofing) technique. In all the manufacturing sector, a lot of small-small problem is affected the product quality and cost. In this paper the 70×90×10 oil seal mixing poka-yoke is solved for the improvement of quality of the product and save the manufacturing cost.